2003
DOI: 10.2337/diacare.26.8.2288
|View full text |Cite
|
Sign up to set email alerts
|

Biologic and Quality-of-Life Outcomes From the Mediterranean Lifestyle Program

Abstract: OBJECTIVE -Few multiple lifestyle behavior change programs have been designed to reduce the risk of coronary heart disease in postmenopausal women with type 2 diabetes. This study tested the effectiveness of the Mediterranean Lifestyle Program (MLP), a comprehensive lifestyle self-management program (Mediterranean low-saturated fat diet, stress management training, exercise, group support, and smoking cessation), in reducing cardiovascular risk factors in postmenopausal women with type 2 diabetes.RESEARCH DESI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
207
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(215 citation statements)
references
References 23 publications
(21 reference statements)
7
207
0
1
Order By: Relevance
“…Consistent with our findings, results from a nutritional intervention, which promoted the traditional MEDdiet over a period of 24 months, reported a significant reduction in body weight (À5.1%) and waist circumference (À2.2%) (Esposito et al, 2004). Two other studies have reported similar findings in response to a nutritional intervention promoting the MEDdiet (Castagnetta et al, 2002;Toobert et al, 2003). Surprisingly, our results did not demonstrate a significant relationship between changes in caloric intake and changes in body weight or waist circumference, although mean caloric intake decreased in response to the intervention.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, results from a nutritional intervention, which promoted the traditional MEDdiet over a period of 24 months, reported a significant reduction in body weight (À5.1%) and waist circumference (À2.2%) (Esposito et al, 2004). Two other studies have reported similar findings in response to a nutritional intervention promoting the MEDdiet (Castagnetta et al, 2002;Toobert et al, 2003). Surprisingly, our results did not demonstrate a significant relationship between changes in caloric intake and changes in body weight or waist circumference, although mean caloric intake decreased in response to the intervention.…”
Section: Discussionsupporting
confidence: 91%
“…Strengths of this study are that it was multicentre, thus less dependent on local factors, and of larger size and longer duration than other exercise intervention trials in patients with type 2 diabetes [24][25][26][27], including those assessing QoL and well-being measures [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…From a long-term perspective, lifestyle modification might be better maintained if associated with improvement in quality of life (QoL), but results from previous trials investigating the impact of structured exercise counselling or supervised training on physical and mental health and well-being in diabetic patients are inconclusive [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We did, however, observe benefits of resistance exercise training for the physical component. In another randomised controlled trial in 279 post-menopausal women with type 2 diabetes mellitus [30], Toobert found that after 6 months participation in a self-directed physical activity programme including moderate aerobic activity for 30 min most days of the week and ten strength-training exercises performed twice per week improvements for HbA 1c , BMI and plasma fatty acids were significantly greater in the intervention group than in the usual care group. There were no significant between-group (experimental vs usual care) differences in the physical and mental health scores of the MOS-12, a brief version of the SF-36.…”
Section: Discussionmentioning
confidence: 99%